التزامات الناقل البحري للبضائع في التشريع الجزائري - عادل, بله باسي (جامعة الوادي.University eloued, 2021)
"يعد موضوع بحثنا التزامات الناقل البحري للبضائع في التشريع الجزائري من أبرز المواضيع في القانون البحري، وخاصة في ظل انفتاح الدول على التجارة الدولية واعتمادها بشكل كبير على النقل البحري. يترتب على عاتق الناقل البحري للبضائع بموجب عقد النقل البحري التزامات اتجاه الشاحن وتهدف الى تسليم البضاعة سليمة للمرسل اليه أو ممثله، واخلال الناقل البحري بهذه الواجبات سيعرضه الى المساءلة القانونية، ولحماية الناقل سعت التشريعات الوطنية والدولية الى وضع حالات وشروط للإعفاء من المسؤولية. ""The topic of our research is the Obligations of the shipping carrier for the cargo in Algerian legislation, one of the most prominent topics in maritime law, especially in light of the openness of countries to international trade and their heavy dependence on maritime transport. The marine carrier of cargo under the maritime transport contract has obligations towards the shipper and aims to deliver the cargo intact to the consignee or his representative, and the breach of these duties by the marine carrier will expose him to legal accountability, and to protect the carrier, national and international legislation sought to establish cases and conditions for exemption from liability. "
قانون أعمال
Keywords: التزامات الناقل، النقل البحري، سند الشحن، التسليم، الشاحن، ميناء التفريغ